Human Capital, R&D and Productivity Convergence of European Regions. A spatial analysis of RHOMOLO's semi endogenous growth approach. - Fabio Manca; Giuseppe Piroli (European Regional Science Association (ERSA), 2011)
The aim of the paper is to test the Benhabib and Spiegel (2005) productivity (TFP) catch-up framework on European regions. Differences in the stock of human capital across regions are hypothesized to be the cause of differences in the speed by which follower regions converge and catch-up with the technology frontier. We find robust empirical evidence for this hypothesis. Also, we find evidence of complementarities between R&D expenditures and human capital accumulation for which R&D impacts TFP growth as long as a critical mass for the stock of human capital is reached. The results are robust to sectoral disaggregations and to the choice of a country or sectoral specific leader in the TFP gap computation and to control for spatial dependence across European regions.
Keywords: 330